2020
DOI: 10.4103/gmit.gmit_84_19
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of natural orifice transluminal endoscopic surgery in gynecology practice: Single-surgeon experience

Abstract: Objectives: Natural orifice transluminal endoscopic surgery (NOTES) has been performed in gynecology practice for the surgical treatment of ovarian cysts, uterine fibroids, ectopic pregnancies, adnexal masses, and pelvic organ prolapse. The aim of this study is to evaluate the intraoperative and postoperative outcomes of patients who underwent NOTES for gynecological diseases. Materials and Methods: This study was a retrospective clinical study. The data of 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The VAS scores at the 12 th and 24 th hours did not differ between groups, but the operation time and hospital stay were lower in the VaNOTES group [12]. The change in VAS scores in our study is similar to that reported by Kaya et al [4]. Santos et al [13] reported that only the closure of the vaginal cuff in VaNOTES caused this difference in VAS scores compared to the closure of 3-4 trocar accesses in the abdomen in conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The VAS scores at the 12 th and 24 th hours did not differ between groups, but the operation time and hospital stay were lower in the VaNOTES group [12]. The change in VAS scores in our study is similar to that reported by Kaya et al [4]. Santos et al [13] reported that only the closure of the vaginal cuff in VaNOTES caused this difference in VAS scores compared to the closure of 3-4 trocar accesses in the abdomen in conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…The largest hysterectomy series treated with VaNOTES in the literature was reported by Lee et al In this study, the average operative time was 88 minutes, and the mean hospital stay was 2.8 days [6]. In the study of Kaya et al [4] comparing the patients who underwent hysterectomy/BSO and adnexectomy with VaNOTES, the mean uterine weight, operation time, and hospital stay were 298 g, 85 minutes, and 2 days, respectively. To the best of our knowledge, our study is the second largest series in the literature, and similar findings were found in the VaNOTES protocol among hysterectomy patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The clinical feasibility of vNOTES was demonstrated in 2007 [ 5 ]. Since then, this minimally invasive surgical technique has been successfully performed for many gynecological pathologies, reportedly resulting in superior cosmetic outcomes and faster postoperative recovery compared to those obtained by TU-LESS, despite relatively restricted visualization and operative space [ [6] , [7] , [8] , [9] , [10] ]. However, because the literature regarding the outcomes of ovarian vNOTES is scant, and none of the existing studies have reported on sufficiently large cohorts [ 3 , 7 ], clinical evidence of its outcomes is lacking, and there are many concerns regarding the technical difficulty, safety, and feasibility of this procedure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopy initiated the era of minimally invasive surgery, while transvaginal natural orifice transluminal endoscopic surgery (V-NOTES) was a further step to the field. Nowadays, V-NOTES have been successfully applied in gynecological benign lesions, even malignant diseases [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ] [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. According to the recommendations of American College of Obstetricians and Gynecologists, V-NOTES should be performed “whenever is feasible” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%